2016
DOI: 10.1038/cddis.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and neurorestorative potential of xenon

Abstract: International audienceXenon is a monatomic gas that belongs to the family of noble gases. Like other noble gases, it is characterized by a filled valence shell and therefore exhibits low chemical reactivity. Paradoxically, xenon possesses a remarkable spectrum of biological effects that are of potential clinical interest. Xenon is an approved anesthetic drug with analgesic properties. In addition to that xenon is neuroprotective in preclinical models of focal and global brain ischemia, spinal cord ischemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
15
1
1
Order By: Relevance
“…Interestingly, we found that xenon also worked as a trophic factor toward basal forebrain cholinergic neurons, a neuronal population at risk in this disorder (Lavaur et al . ,b).…”
mentioning
confidence: 99%
“…Interestingly, we found that xenon also worked as a trophic factor toward basal forebrain cholinergic neurons, a neuronal population at risk in this disorder (Lavaur et al . ,b).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the strong xenon neuroprotective effects (Metaxa et al, 2014 ; Lavaur et al, 2016a , b ; Zhang et al, 2019a , b ); however, the possible xenon neuroprotective effects and the underlying mechanisms in seizure-induced neuronal injury remain clear. In this study, we assessed the effects of xenon treatment on neuronal injury; moreover, we evaluated the role of autophagy in KA-induced acute generalized seizures and the involved xenon neuroprotective effects.…”
Section: Discussionmentioning
confidence: 98%
“…Excessive excitation of the N-methyl-D-aspartate receptor, which results from extracellular glutamate accumulation, causes acute nerve injury or even death, by activating calpain and the caspase-3 pathway in patients with epilepsy and in animal models of epilepsy (Baudry and Bi, 2016 ; Hoque et al, 2016 ; Ceccanti et al, 2018 ). Xenon treatment regulates the glutamate level by suppressing its uptake and efflux (Lavaur et al, 2016a ). This results in the upregulation of the anti-apoptotic protein Bcl-2 and downregulation of the pro-apoptosis protein Bax.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations